Comparative study of proportional INTEGRAL (PI) and proportional resonant (PR) current controller for single phase inverter / Mohammad Parvez - Mohammad , Parvez (2017)
This research work focuses on the comprehensive analysis of proportional resonant (PR) controller for single-phase inverter. There is an increasing requirement for current-controlled voltage source inverters with very low or zero steady-state error, better transient response and lower total harmonic distortion (THD). The most promising type of current regulator for single-phase inverter is PR controller because it can introduce an infinite gain at a selected resonance frequency such as the fundamental frequency to eliminate the steady-state error, which cannot be achieved by the well- known proportional integral (PI) controller. The PI controller faces problem in both steady-state magnitude error and phase error. In addition, it also has limited disturbance rejection capability, unlike the PR controller, which can also compensate the low-order harmonics. The imperfection in current control scheme results in higher harmonic distortion of the output current. This research presents detail analysis and implementation of PR current controller in single-phase inverter applications such as stand-alone and grid-connected renewable energy systems, energy storage systems and backup power supplies. Thus, the mathematical model of PR controller has been analyzed. In order to realize the important control features over conventional PI controller, PI controller has also been implemented in the same inverter and mathematically analyzed. The performances for both of these controllers have been analyzed in terms of steady-state and transient responses and current harmonics level. The effects of frequency variation on the PR controller performance have also been shown. The experimental result shows that the PR controller achieves zero steady-state error, better transient response and reduces the low-order harmonics distortion of the output current compared to PI controller. The harmonics has further been reduced by incorporating selective harmonic compensation with PR controller. The performances of the implemented controllers are simulated and compared in the widely used software such as the MATLAB/Simulink environment which has reduced the developmental time and cost of the switching system. The experimental results of a 250 W laboratory test set have been implemented to validate the theoretical analysis and control principles of the PR and PI controllers.